Estimation of Natural Variability in Different Pearl Millet (Pennisetum glaucum L.) Sudanese Genotypes - Salih, Manal A. M; Abdallah, Abdalwahab H; Eltigani, Sayadat (International Journal of Sustainable Agricultural Research, 2020)
Millet is grown mostly as the main grain crop in the drier Western Parts of Sudan (Darfur and Kordofan States) where climatic conditions permit only millet production. Also there is a limited cultivation of millet in the Eastern region of the country. Most species of Pennisetum are protogynous, but pearl millet is more conspicuous in this regard. This facilitates the introgression of characters from other annual penicillaries into pearl millet and hence has helped in the genetic enrichment of this species. In this study 20 pearl millet genotypes were collected from different parts of the Sudan with concentration on the western states. They were evaluated to assess the extent of variation among them in morphological and yield parameters, using a randomized complete block design with two replications. The twenty pearl millet genotypes exhibited significant differences in most of the characters studied. Out of the 19 parameters, only yield per tiller panicle and total yield per plant were non-significantly different. There is a noticeable variation, not only among the different genotypes of the same species but also within the same genotype or cultivar. Such variation may be attributed to the open pollination system of this crop